2018
DOI: 10.5897/ajar2015.10008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some Musa accessions in field collection at Ebonyi State University, Abakaliki, Nigeria

Abstract: The study was conducted to characterize and evaluate the agronomic potentials of eight Musa accessions in Ebonyi State University Musa field genebank. Qualitative descriptors were used to characterize the genotypes, while eight growth and yield traits were evaluated. Results indicated that the accessions were similar in thirteen characteristics, but differed in nine traits including pseudostem/foliage pigmentation, pseudostem/foliage waxiness, pseudostem blotching, petiole margin clasping, peduncle hairiness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
2
1
Order By: Relevance
“…The number of ngers per midhand of the bunch ranged from ≤ 12 to ≥ 17 in the present study. However, Vinson et al (2018) reported means ranging from 11.7 to 17.7 for ngers per hand, while Oselebe et al (2018) reported a mean number of ngers ranging from 9.00 to 13.00 with a mean fruit length ranging from 14.60 cm to 21.20 cm, which is smaller than the fruit length range reported in the present work (15 cm ≤ fruit length ≥ 31 cm). Soares et al (2012) reported a positive correlation between fruit length and bunch weight.…”
Section: Genetic Dissimilarity Analysiscontrasting
confidence: 93%
See 3 more Smart Citations
“…The number of ngers per midhand of the bunch ranged from ≤ 12 to ≥ 17 in the present study. However, Vinson et al (2018) reported means ranging from 11.7 to 17.7 for ngers per hand, while Oselebe et al (2018) reported a mean number of ngers ranging from 9.00 to 13.00 with a mean fruit length ranging from 14.60 cm to 21.20 cm, which is smaller than the fruit length range reported in the present work (15 cm ≤ fruit length ≥ 31 cm). Soares et al (2012) reported a positive correlation between fruit length and bunch weight.…”
Section: Genetic Dissimilarity Analysiscontrasting
confidence: 93%
“…This nding corresponds to the ndings of the present study, which reported that 55% of the bracts were retracted and rolled back. In total, 63.64% of the accessions exhibited red, dull purple or yellow outside with pink, dull purple, or yellow inside, similar to the ndings of Oselebe et al (2018).…”
Section: Genetic Dissimilarity Analysissupporting
confidence: 62%
See 2 more Smart Citations